Knowledge about tuberculosis in individuals deprived of liberty of a regional penitentiary in the Zona da Mata Mineira - Brazil - Brasil, Gilberto Caetano; Batista, Rodrigo Siqueira; Gomes, Andréia Patrícia; Colodette, Renata Maria; Oliveira, Deíse Moura de; Moreira, Tiago Ricardo (Ciência e Natura, 2022)
Objective: To evaluate knowledge related to TB and to investigate the predictive factors of the prisoners' knowledge status in a regional penitentiary in the Zona da Mata Mineira - Brazil. Methods: This is a cross-sectional and institutionally based study that was conducted with 729 individuals deprived of their liberty in a regional penitentiary. A questionnaire was applied and the detainees 'knowledge about tuberculosis was obtained from the participants' answers to questions about tuberculosis prevention, transmission and treatment. For data analysis, multiple logistic regression was used. Results: Approximately 40% of the detainees reported not having knowledge about transmission, prevention and treatment of tuberculosis and the lack of knowledge was associated with the following variables: lower education, lower income, closed regime, being the first prison, not having contact with TB outside and inside the prison, not showing symptoms of cough with secretion, weakness and chest pain and not having an HIV test. Conclusion: The lack of knowledge about tuberculosis was associated with education, income, prison terms, first prison, contact with TB outside and inside the prison, symptoms of tuberculosis and HIV testing. The recognition of these factors can contribute to the development of educational interventions aimed at controlling tuberculosis in this population.